Catalytic activity of electrodeposited cobalt oxide films for methane combustion in a micro-channel reactor. (15th November 2018) - Rodrigues, José M.; Ribeiro, M. Filipa; Fernandes, Edgar C.
Highlights: Cobalt oxide films were fabricated by electrodeposition of cobalt nitrate. The cobalt oxide grows into a compact and porous tracery of nanosheets. The cobalt oxide films are catalytically active towards methane combustion. The measured reaction rates are similar to other cobalt-based films in the literature. Abstract: This paper studies the catalytic combustion of a methane-air mixture inside a micro-channel reactor coated with cobalt oxide (Co3 O4 ) film. The Co3 O4 was coated on the reactor channels by an inexpensive electrodeposition method. A cohesive film with large accessible surface area was fabricated with the method described, which allowed the control of the film thickness. Complete combustion of methane was achieved at 760 °C. The catalytic activity profiles obtained suggest that the reaction is carried only via catalytic combustion up to 600 °C, while both gas-phase and catalytic combustion might occur simultaneously at higher temperatures. The measured catalytic reaction rate per unit area was aligned with the reaction rate reported for similar reactors and operating conditions. Results showed that the catalytic films did not deactivate after a total of 50 h of cyclic operation. Tests with different reactants concentration revealed a first order dependence of the reaction rates for methane concentration and a near zero-order dependence on the oxygen concentration, at 600 °C. The measured data was successfully fitted by a chemistry model proposed in the literature. Overall, this work highlights the potential of using inexpensive electrodeposited films of Co3 O4 on micro-channel reactors for combustion of hydrocarbons.